Duration of Listening to BTS Music with Psychological Well-Being in BTS Fans - Ester Kinny Pyghaiswati Allosau; Christiana Hari Soetjiningsih (Journal La Sociale, 2024)
This correlational quantitative research aims to determine the relationship between the duration of listening to BTS music and the psychological well-being of BTS fans in Indonesia (known as Army Indonesia). The study included 102 participants who have been fans for a minimum of 2 years, and data was collected using a Google Form provided by the researcher. The measurement tools used were an interval scale to assess the daily duration of listening to BTS music and the Ryff Psychological Well-Being (RPWB) scale to measure psychological well-being. The research results indicate a significant positive correlation between the duration of listening to BTS music and the psychological well-being of BTS fans in Indonesia, with an "r" value of 0.171 and a significance value of 0.043 (p < 0.05). This implies that the longer the duration of listening to BTS music, the higher the level of psychological well-being among fans, and vice versa. The duration of listening to BTS music contributes to fans' psychological well-being by 2,9%. In summary, this research suggests that there is a statistically significant positive relationship between the amount of time spent listening to BTS music and the psychological well-being of BTS fans in Indonesia, with longer listening durations associated with higher levels of psychological well-being.